Psychological well-being of palliative care professionals: Who cares? - Moreno-Milan, Beatriz (Palliat Support Care, 2021)
BACKGROUND. Traditionally, the psychological well-being of healthcare workers has been taken for granted — it has even been considered a part of the requirements that were demanded of them. When these professionals have experienced suffering and psychological depletion, they have been held accountable for this suffering, adopting an individualistic and reductionist viewpoint focused only on the professional. This approach has become obsolete due to its proven ineffectiveness, especially from an ethics of responsibility and organization viewpoint. CONTEXT. The psychological well-being of the healthcare worker (and its opposites: suffering, exhaustion, and disenchantment) is advantageous to the professional’s commitment to the institution, to their work performance, and to their personal life. OBJECTIVE. The objective of this paper is to reflect on the psychological suffering of the palliative care professional. METHOD. We will reflect on the three levels of responsibility that influence such suffering (micro-meso-macro-ethical; worker-environment-institution). RESULTS. We will propose a global strategy for the care of psychological well-being supported by scientific evidence and key references. SIGNIFICANCE OF RESULTS. We conclude with some contributions on what we have learned and still have to learn on this topic.